2014
DOI: 10.1111/pce.12410
|View full text |Cite
|
Sign up to set email alerts
|

Role of aquaporins in determining transpiration and photosynthesis in water‐stressed plants: crop water‐use efficiency, growth and yield

Abstract: The global shortage of fresh water is one of our most severe agricultural problems, leading to dry and saline lands that reduce plant growth and crop yield. Here we review recent work highlighting the molecular mechanisms allowing some plant species and genotypes to maintain productivity under water stress conditions, and suggest molecular modifications to equip plants for greater production in water-limited environments. Aquaporins (AQPs) are thought to be the main transporters of water, small and uncharged s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
147
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(156 citation statements)
references
References 106 publications
5
147
1
3
Order By: Relevance
“…Isohydric species reduce stomatal conductance as soil water decreases and the demand for water in the atmosphere increases during drought conditions, maintaining relatively constant midday leaf water potential. In contrast, anisohydric species allow midday leaf water potential to decline as soil dries during drought, thus maintaining stomatal conductance and CO 2 assimilation [10,58,59]. Trees experiencing long-term, persistent drought in our study did not maintain leaf water potentials or reduce stomatal conductance, which could indicate an anisohydric response strategy to long-term drought conditions.…”
Section: Discussioncontrasting
confidence: 61%
“…Isohydric species reduce stomatal conductance as soil water decreases and the demand for water in the atmosphere increases during drought conditions, maintaining relatively constant midday leaf water potential. In contrast, anisohydric species allow midday leaf water potential to decline as soil dries during drought, thus maintaining stomatal conductance and CO 2 assimilation [10,58,59]. Trees experiencing long-term, persistent drought in our study did not maintain leaf water potentials or reduce stomatal conductance, which could indicate an anisohydric response strategy to long-term drought conditions.…”
Section: Discussioncontrasting
confidence: 61%
“…Indeed, recent studies have suggested that cell shrinkage with dehydration, and/or deactivation of membrane aquaporins outside the xylem, could strongly reduce K leaf (Kim and Steudle, 2007;Shatil-Cohen et al, 2011;Pantin et al, 2013;Scoffoni et al, 2014;Moshelion et al, 2015;Sade et al, 2015). Yet, the vulnerability of K x and K ox , and their influences on K leaf decline with dehydration, have not been clearly disentangled.…”
mentioning
confidence: 99%
“…aquaporins [AQPs]; for review, see Moshelion et al, 2014). AQPs are considered to be key channel proteins for the transport of water, small and uncharged solutes, and CO 2 through plant cell membranes (Tyerman et al, 2002;Maurel et al, 2008).…”
mentioning
confidence: 99%